Network simulators parametric comparison for network mobility management - Aman, Azana Hafizah Mohd; Hassan Abdalla Hashim, Aisha; Abdullah, Azween; Ramli, Huda Adibah Mohd; Islam, Shayla (2016)
It is generally known that network simulator is a program used to verify new or existing network architecture and its activities. Basically network simulator helps to implement the virtual part of network research. This has save a lot of cost on analysis as the results of a network simulator is very close to real network cases. In recent researches, new models and prototypes are introduced to enable latest technologies support on network simulators. Some well-known network simulators are NS2, NS3, OMNET++ and QUALNET. As network research continues to grow rapidly, there is a need to analyze the supports and services offered by each network simulators. The objective of this paper is to investigate and analyze these network simulators in term of network mobility supports. This is because network mobility management has become a crucial topic in networking research. In selecting the right network simulators, issues such as CPU utilization, memory usage, computation time, feasibility, scalability and affordability need to be wisely studied. Using qualitative analysis this paper highlights the strengths and the limitations of these network simulators. The qualitative evaluations of these simulators are hereby presented.